The Determinants of Firm Competitiveness: Evidence from the Indian Manufacturing Sector. Issue 2 (4th May 2022) - Sahoo, Pradipta Kumar; Le, Viet; Rath, Badri Narayan
Abstract: This paper investigates the determinants of competitiveness of Indian manufacturing sector. First, based on multi-variate Industrial Competitiveness Index (ICI), the result reveals that capital-intensive firms are more competitive than labor-intensive firms. Second, the results also indicate that foreign-owned firms are more competitive than domestic firms. Third, the determinants of competitiveness derived from Feasible Generalized Least Squares (FGLS) and dynamic panel GMM model indicate that the firms' external factors such as Information and Communication Technology (ICT) and infrastructure positively affect manufacturing firms' competitiveness. However, internal factors such as firm age and debt have a negative effect on Indian manufacturing firms' competitiveness, but the lag effect of R&D intensity and advertisement intensity has a positive impact on firms' competitiveness. Our results are robust in different sub-categories based on industry sub-sectors and firm ownership structure.